Approximate Solution for the Electrohydrodynamic Flow in a Circular Cylindrical Conduit. (15th March 2012) - Khan, Najeeb Alam; Jamil, Muhammad; Mahmood, Amir; Ara, Asmat
Abstract : This paper considers the nonlinear boundary value problem (BVP) for the electrohydrodynamic flow of a fluid in an ion drag configuration in a circular cylindrical conduit. The velocity field was solved using the new homotopy perturbation method (NHPM), considering the electrical field and strength of the nonlinearity. The approximate analytical procedure depends only on two components and polynomial initial condition. The analytical solution is obtained and the numerical results presented graphically. The effects of the Hartmann electric number ℋa and the strength of nonlinearity α are discussed and presented graphically. We also compare this method with numerical solution (N.S) and show that the present approach is less computational and is applicable for solving nonlinear boundary value problem (BVP).